I need to solve:

$$\int \sqrt{x^2-3} \, dx.$$

So I use the substitution:

$$x=\frac{\sqrt 3}{\cos(t)}$$

$$dx= \frac{\sqrt 3 \sin(t) \, dt}{\cos^2(t)} $$

and I get

$$3\int \frac{\sqrt{\frac1 {\cos^2(t)}-1}\cdot\sin(t) \, dt}{\cos^2(t)}. $$

So I get

$$3\int \frac{\sin(t)\tan(x)\,dx}{\cos^2(x)},$$ that is $(\sin(t)\sin(t)/\cos(t))/\cos^2(t)$ and finally I have

$$3\int \frac{\sin^2(t)\,dt}{\cos^3(t)}$$

Substitute $\sin(t)=s$, so $\cos(t) \, dt=ds$. The integral becomes

$$3 \int \frac{s^2\,ds}{(1-s^2)^2};$$ $$dt= \frac{ds}{\cos t}$$

So problem is I don't know how do I get from this $\sqrt{(1/\cos^2(t))-1} = \tan(t);$

It was stupid question idk how I didn't saw that nvm, after that use partial integration $u=s$, $du=ds$, $v=1/(1-s^2)$ and i get $s/2(1-s^2)-1/2$ integral of $ds/(1-s^2)$ and the solution is $3/2(s/1-s^2-1/2\ln(1+s/1-s)$

  • 3
    $\begingroup$ This is an integral, not an integer. $\endgroup$ – Arthur Jul 28 '16 at 17:25
  • $\begingroup$ It is a bit hard to read and understand the question! $\endgroup$ – Majid Jul 28 '16 at 17:25
  • $\begingroup$ $$\text{Integer}=0,1,-1,2,-2,3,-3,\ldots\\ \text{Integral}=\int$$ $\endgroup$ – user228113 Jul 28 '16 at 17:25
  • $\begingroup$ Please reedit. This is unreadable. What the heck is tgt? $\endgroup$ – fleablood Jul 28 '16 at 17:26
  • 2
    $\begingroup$ I did not read anything but the last line, so this might not be helpful. $$\sqrt{\frac1{\cos^2 x}-1}=\sqrt{\frac{1-\cos^2x}{\cos^2x}}$$ and here's where you remember what $1-\cos^2x$ is. $\endgroup$ – user228113 Jul 28 '16 at 17:29

Note that $$\cos^2 \theta + \sin^2 \theta = 1$$ so dividing both sides by $\cos^2 \theta$ gives $$1 + \tan^2 \theta = \frac{1}{\cos^2 \theta} \iff \frac{1}{\cos^2 \theta} - 1 = \tan^2 \theta$$

And so, taking the square root of both sides gives you what you want.

  • 2
    $\begingroup$ Since the main question appeared to be expressed as "So problem is I don't know how do I get from this $\sqrt{(1/\cos^2(t))-1} = \tan(t);$", this is the only really good answer so far. $\qquad$ $\endgroup$ – Michael Hardy Jul 28 '16 at 22:06

Hint. As you have suggested, the change of variable $$ x=\frac{\sqrt{3}}{\cos t},\quad dx=\frac{\sqrt{3}\sin t}{\cos^2 t}\:dt, $$ gives $$ \begin{align} \int \sqrt{x^2-3}\:dx&=\sqrt{3}\int\sqrt{\frac3{\cos^2 t}-3}\:\cdot \frac{\sin t}{\cos^2 t}\:dt \\\\&=3\int\sqrt{\frac{1-\cos^2 t}{\cos^2 t}}\:\cdot \frac{\sin t}{\cos^2 t}\:dt \\\\&=3\int \frac{\sin^2 t}{\cos^3 t}\:dt \\\\&=3\int \frac{\sin^2 t\: \cos t}{(1-\sin^2 t)^2}\:dt \\\\&=3\int \frac{s^2}{(1-s^2)^2}\:ds \end{align} $$ can you take it from here?

  • $\begingroup$ I think at some point the OP arrived at your last line already. $\endgroup$ – user99914 Jul 28 '16 at 17:43
  • $\begingroup$ @ArcticChar Yes, I've seen it. that's why I ask him if it is Ok. $\endgroup$ – Olivier Oloa Jul 28 '16 at 17:44
  • $\begingroup$ That big sqrt how do i get a tan(t) of it ,,,,,,1-cos^2t/cos^2t $\endgroup$ – user5927353 Jul 28 '16 at 17:47
  • $\begingroup$ @user5927353 Like this: $$\sqrt{\frac{1-\cos^2 t}{\cos^2 t}}=\sqrt{\frac{\sin^2 t}{\cos^2 t}} =\tan t$$ Is it Ok? we assume $\tan t\ge0$. $\endgroup$ – Olivier Oloa Jul 28 '16 at 17:48
  • $\begingroup$ Idk how i didn't see this......,and how can i write like that with? $\endgroup$ – user5927353 Jul 28 '16 at 17:49

$3\int \frac {\sin^2(t)}{\cos^3(t)} dt$

Rather than a substitution I suggest you do this.

$3\int \tan^2 t \sec t dt$

integration by parts:

$u = \tan t, dv = \sec t \tan t dt\\ du = sec^2 t dt, v = sec t$

$3\sec t \tan t - 3\int \sec^3t dt\\ 3\sec t \tan t - 3\int (\tan^2 t - 1)\sec t dt\\ 3\sec t \tan t + 3 \int \sec t dt - 3\int \tan^2 t \sec t dt\\ 3\sec t \tan t + 3 \ln |\sec t + \tan t| - 3\int \tan^2 t \sec t dt$

And we have come full circle:

$3\int \tan^2 t \sec t dt = 3\sec t \tan t + 3 \ln |\sec t + \tan t| - 3\int \tan^2 t \sec t dt\\ 3\int \tan^2 t \sec t dt = I\\ I = 3\sec t \tan t + 3 \ln |\sec t + \tan t| - I\\ 2 I = 3\sec t \tan t + 3 \ln |\sec t + \tan t|\\ I = \frac 32 \sec t \tan t + \frac 32 \ln |\sec t + \tan t|+C$

Alternatively, If you want to stick with your initial approach.

$\int \frac {s^2}{(1-s^2)^2} ds$

Find a partial fraction decomposition:

$\frac {s^2}{(1-s^2)^2} = \frac A{1-s} +\frac B{1+s} + \frac C{(1-s)^2} + \frac D{(1-s)^2}$

And that will integrate to

$-A\ln (1-s) + B\ln(1+s) + C(1-s)^{-1} - D(1+s)^{-1} + c$ (sorry do double use the same letter)

Hopefully, the two answers are equivalent.

  • $\begingroup$ Can you tell me how can i write in that format where is everything alot easier to read?(math format) – $\endgroup$ – user5927353 Jul 28 '16 at 18:01

First rescale

$$\int \sqrt{x^2-3} \, dx=3\int \sqrt{t^2-1} \, dt.$$

Then by parts,

$$\int \sqrt{t^2-1} \, dt=t\sqrt{t^2-1}-\int\frac{t^2}{\sqrt{t^2-1}}dt=t\sqrt{t^2-1}-t-\int\frac{dt}{\sqrt{t^2-1}}.$$

In the last integral, you should recognize the derivative of $\text{arcosh }t$.

  • 1
    $\begingroup$ Well, if the question is "So problem is I don't know how do I get from this $\sqrt{(1/\cos^2(t))-1} = \tan(t);$", then I don't think this addresses it. $\qquad$ $\endgroup$ – Michael Hardy Jul 28 '16 at 22:05

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.